Maintaining Sustainable Tourism through Management of Carbon Gas Emissions concerning Green Growth 2050 Bali Roadmap - Dewantara, Made Handijaya; Gaud, Christian Enriquez (Journal of Indonesian Tourism, Hospitality and Recreation, 2022)
ABSTRACTThis study will provide insight in managing the carbon gas emission that Bali tourism development could raise. It will be related to the Green Growth Roadmap, released by the Provincial Government of Bali. Through an in-depth interview and desk research study, followed by a qualitative descriptive analysis, some strategies could be found that could be a way for the government to execute the carbon gas emission policy. We suggest an intensive collaboration between government and industry by setting a progressive target to reduce greenhouse gas emissions and determining a specific number. This article also suggests a mechanism by establishing a periodic report and assistance to anticipate gas emissions. Our research also found that promoting education and explaining the benefits of measuring and reducing greenhouse gas emissions. Conducting a research center dedicated to research and communication to help the business sector reduce emissions, including information in technology, facilitated by the academician. Last, creating an integrated certified system called "Authentic Green Bali." We also recommend to valuate carbon expenditure schemes for air, land, and accommodation transportation.ABSTRAKStudi ini akan membantu dalam mengelola emisi gas karbon yang dapat ditimbulkan oleh pengembangan pariwisata Bali. Hal itu terkait dengan Green Growth Roadmap yang dikeluarkan oleh Pemerintah Provinsi Bali. Melalui wawancara mendalam dan studi pustaka, dilanjutkan analisis deskriptif kualitatif, dapat ditemukan beberapa strategi yang dapat menjadi jalan bagi pemerintah untuk mengeksekusi kebijakan emisi gas karbon. Kami menyarankan kolaborasi intensif antara pemerintah dan industri dengan menetapkan target progresif untuk mengurangi emisi gas rumah kaca dan menentukan jumlah tertentu. Artikel ini juga menyarankan mekanisme dengan membuat laporan berkala dan bantuan untuk mengantisipasi emisi gas. Penelitian kami juga menemukan bahwa mempromosikan pendidikan dan menjelaskan manfaat mengukur dan mengurangi emisi gas rumah kaca. Menyelenggarakan pusat penelitian yang didedikasikan untuk penelitian dan komunikasi untuk membantu sektor bisnis mengurangi emisi, termasuk informasi di bidang teknologi, yang difasilitasi oleh akademisi. Terakhir, membuat sistem bersertifikat terintegrasi yang disebut "Authentic Green Bali". Kami juga merekomendasikan menilai skema pengeluaran karbon untuk transportasi udara, darat, dan akomodasi.